Voice of Dissent: Negation of Heterosexuality in Adrienne Rich’s Poetry - Bhusal, Tilak (Vox Batauli, 2023)
This article explores the opposition of heterosexuality in Adrienne Rich’s poems. Rich has questioned the heterosexual institutions in her poetry and has consciously worked to re-create women’s identity taking an oppositional stance towards heterosexuality and trying to establish women's positional stance. Heterosexuality as a political institution is so pervasive that it has not only controlled women's bodies by various means but also has controlled their consciousness. It proved that women should seek their primary emotional and erotic ties in themselves to have women-identified experiences and freedom. Rich’s poems; “Rape”, “Aunt Jennifer’s Tigers”, “Twenty-one Love Poems I” and “Diving into the Wreck” are examined through radical feminism and lesbian perspectives.